Characteristics in Initial Sandplay of Optimal and Non-optimal Family Functioning Among High School Students - Qiu-qiang, Zheng; Guang-zhi, Zhuo; Qi-zhe, Zhang (Frontiers in Psychology, 2022)
Objective: The purpose of this study is to explore the characteristics of the initial sandplay of high school students with poor family function, by studying the initial sandplay of high school students with different levels of family function, so as to provide the basics for the psychological assessment and intervention of high school students. Significance: To provide data support for high school students' mental health education and sandplay therapy, and to apply sandplay as an intervention method to play a healing role in high school mental health work. Methods: High school students (N=345) were divided into 11 groups and participated in a sandplay experiment for eight weeks from February to March 2021. Each group completed the Chinese version of the Epstein et al. Family Assessment Device. Samples with scores of one standard deviation below and above the sample mean were placed in the low family functioning group (n=30; 15 girls) or high family functioning group (n=30; 15 girls), respectively. The initial sandplay was evaluated on multiple dimensions using an established coding system. Results: Samples with low family functioning used fewer animal figurines in their sandplay (t=2.176, p<.05); had more family scenes (2=4.356, p< 0.05); fewer rural scenes (2=4.344, p<.05); and fewer healing themes (t=-2.336, p<.05). In particular, there were fewer examples of connected healing themes (2=7.500, p<.05); in-depth healing themes (2=5.455, p<0.05); and more hindered trauma themes (2=4.812, p<.05). Logistic regression analysis was conducted using the sandplay characteristics as predictors of group membership. Using forward stepwise selection, themes of hindered trauma (B=-2.030) and connected healing (B=1.765) were shown to be significant predictors of group membership (F=17.784, P<.01, △R2=.214). Conclusion: Students who reported high and low family functioning showed significant differences in their sandplay characteristics. We propose sandplay characteristics can help identify low family functioning of adolescents during psychological evaluations.